Intercultural learning in language education and beyond : evolving concepts, perspectives and practices - McConachy, Troy, 1980-; Golubeva, Irina; Wagner, Manuela (Educator) (Bristol ; Jackson : Multilingual Matters, 2022)
"This book provides a contemporary and critical examination of the theoretical and pedagogical impact of Michael Byram's pioneering work on intercultural communicative competence and intercultural citizenship. The book offers comprehensive, up-to-date and accessible knowledge for researchers, teachers, teacher-trainers and students"--
Includes bibliographical references and index.
ENH
Keywords: Byram, Michael; Language and languages -- Study and teaching; Intercultural communication -- Study and teaching; Multicultural education